KESIAPAN AKSES TEKNOLOGI INFORMASI DAN KOMUNIKASI PESERTA DIDIK DALAM MENDUKUNG MANAJEMEN PENDIDIKAN DIGITAL DI INDONESIA - Ansori Zaini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The digital transformation of education in Indonesia has prompted the implementation of Coding and Artificial Intelligence (AI) learning as mandated by Ministerial Regulation No. 13 of 2025. However, this policy faces serious challenges as students' readiness in accessing information and communication technology (ICT) has not been comprehensively examined using national-level data. This study aims to analyze students' ICT access readiness in supporting digital education transformation in Indonesia. A descriptive quantitative approach was employed using secondary data from the National Socioeconomic Survey (Susenas) of March 2025 and the Education Data System (Dapodik) of 2022, analyzed through the International Telecommunication Union (ITU) digital skills framework. The findings reveal that although mobile phone and internet access among students is relatively high, the use of computers or laptops remains very low and internet usage is still dominated by entertainment activities. The majority of students remain at the basic digital skills level, whereas Coding and AI learning demands advanced digital skills, indicating a significant gap between policy targets and students' actual digital readiness. These findings imply that strengthening ICT infrastructure, expanding computer access in schools, and developing digital literacy are essential prerequisites before Coding and AI learning policies can be implemented optimally and equitably across all educational institutions in Indonesia. ABSTRAK Transformasi pendidikan digital di Indonesia mendorong implementasi pembelajaran Koding dan Kecerdasan Artifisial (KA) sebagaimana diatur dalam Permendikdasmen Nomor 13 Tahun 2025. Namun, kebijakan ini berpotensi menghadapi kendala serius karena kesiapan akses teknologi informasi dan komunikasi (TIK) peserta didik belum pernah dikaji secara komprehensif berbasis data nasional. Penelitian ini bertujuan menganalisis kesiapan akses TIK peserta didik dalam mendukung transformasi pendidikan digital di Indonesia. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan memanfaatkan data sekunder Susenas Maret 2025 dan Dapodik 2022, dianalisis menggunakan kerangka keterampilan digital International Telecommunication Union (ITU). Hasil penelitian menunjukkan bahwa meskipun akses telepon seluler dan internet peserta didik sudah tinggi, penggunaan komputer atau laptop masih sangat rendah dan pemanfaatan internet masih didominasi oleh hiburan. Mayoritas peserta didik masih berada pada level basic digital skills, sementara pembelajaran Koding dan KA menuntut penguasaan advanced digital skills, sehingga terdapat kesenjangan signifikan antara target kebijakan dan kesiapan digital peserta didik. Temuan ini mengimplikasikan perlunya penguatan infrastruktur TIK, pemerataan akses komputer, dan pengembangan literasi digital sebelum kebijakan pembelajaran Koding dan KA dapat diimplementasikan secara optimal dan merata di seluruh satuan pendidikan Indonesia.